2019
DOI: 10.1021/acs.inorgchem.9b02827
|View full text |Cite
|
Sign up to set email alerts
|

Ground State and Optical Excitations in Compounds with Tetragonal CuF64– Units: Insight into KAlCuF6 and CuFAsF6

Abstract: It has been argued that AAlCuF 6 (A = K, Cs) and CuFAsF 6 are the only known crystals that exhibit compressed CuF 6 4− units due to the Jahn−Teller effect. However, no grounds for this singular behavior have yet been reported. By means of first-principles calculations on such compounds and the isomorphous compounds involving Zn 2+ ions instead of Cu 2+ , we prove that neither the ground state nor the equilibrium geometry of CuF 6 4− complexes in KAlCuF 6 and CuFAsF 6 is the result of a Jahn−Teller effect. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Compressed tetragonal CuF 6 4– units are formed in KAlCuF 6 or CuFAsF 6 pure compounds in addition to Cu 2+ -doped crystals. , By contrast, in CuF 2 or A 2 CuF 4 (A = K, Na), the tetragonally compressed CuF 6 4– units undergo an additional orthorhombic distortion, favored by the existence of adjacent complexes which share F – ligands. ,, An orthorhombic instability also takes place in copper Tutton salts and in NH 4 Cl:CuCl 4 (H 2 O) 2 2– . , …”
Section: Introductionmentioning
confidence: 99%
“…Compressed tetragonal CuF 6 4– units are formed in KAlCuF 6 or CuFAsF 6 pure compounds in addition to Cu 2+ -doped crystals. , By contrast, in CuF 2 or A 2 CuF 4 (A = K, Na), the tetragonally compressed CuF 6 4– units undergo an additional orthorhombic distortion, favored by the existence of adjacent complexes which share F – ligands. ,, An orthorhombic instability also takes place in copper Tutton salts and in NH 4 Cl:CuCl 4 (H 2 O) 2 2– . , …”
Section: Introductionmentioning
confidence: 99%
“…As in the case of CuFAsF 6 , [11] the [CuF 6 ] 4− octahedra in CuFSbF 6 are considerably compressed with two shorter Cu−F bonds (2×1.8410(9) Å) within the [CuF 5 ] n 3n− chains and four longer Cu−F(Sb) bonds (4×2.120(2) Å). A recent study suggested that the local distortion of the CuF 6 octahedra in CuFAsF 6 is unlikely to be due to a Jahn‐Teller effect [14] . In contrast, it was shown that the internal electric field, created by the rest of the lattice ions upon the localized electrons in the complex, plays an important role in understanding this matter [14] …”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that the local distortion of the CuF 6 octahedra in CuFAsF 6 is unlikely to be due to a Jahn‐Teller effect [14] . In contrast, it was shown that the internal electric field, created by the rest of the lattice ions upon the localized electrons in the complex, plays an important role in understanding this matter [14] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations